Cross-sectional and longitudinal associations between athlete burnout, insomnia, and polysomnographic indices in young elite athletes - Gerber, M.; Best, S.; Meerstetter, F.; Isoard-Gautheur, S.; Gustafsson, H.; Bianchi, R.; Madigan, D. J.; Colledge, F.; Ludyga, S.; Holsboer-Trachsler, E.; Brand, S. (Journal of Sport & Exercise Psychology, 2018)
Few studies have examined the association between sleep and burnout symptoms in elite athletes. We recruited 257 young elite athletes (Mage = 16.8 years) from Swiss Olympic partner schools. Of these, 197 were reassessed 6 months later. Based on the first assessment, 24 participants with clinically relevant burnout symptoms volunteered to participate in a polysomnographic examination and were compared with 26 (matched) healthy controls. Between 12% and 14% of young elite athletes reported burnout symptoms of potential clinical relevance, whereas 4-11% reported clinically relevant insomnia symptoms. Athletes with clinically relevant burnout symptoms reported significantly more insomnia symptoms, more dysfunctional sleep-related cognitions, and spent less time in bed during weeknights (p < .05). However, no significant differences were found for objective sleep parameters. A cross-lagged panel analysis showed that burnout positively predicted self-reported insomnia symptoms. Cognitive-behavioral interventions to treat dysfunctional sleep-related cognitions might be a promising measure to reduce subjective sleep complaints among young elite athletes.